Binding of Integrin α6β4 to Plectin Prevents Plectin Association with F-Actin but Does Not Interfere with Intermediate Filament Binding - Geerts, Dirk (The Rockefeller University Press, 1999)
Hemidesmosomes are stable adhesion complexes in basal epithelial cells that provide a link between the intermediate filament network and the extracellular matrix. We have investigated the recruitment of plectin into hemidesmosomes by the α6β4 integrin and have shown that the cytoplasmic domain of the β4 subunit associates with an NH(2)-terminal fragment of plectin that contains the actin-binding domain (ABD). When expressed in immortalized plectin-deficient keratinocytes from human patients with epidermol- ysis bullosa (EB) simplex with muscular dystrophy (MD-EBS), this fragment is colocalized with α6β4 in basal hemidesmosome-like clusters or associated with F-actin in stress fibers or focal contacts. We used a yeast two-hybrid binding assay in combination with an in vitro dot blot overlay assay to demonstrate that β4 interacts directly with plectin, and identified a major plectin-binding site on the second fibronectin type III repeat of the β4 cytoplasmic domain. Mapping of the β4 and actin-binding sites on plectin showed that the binding sites overlap and are both located in the plectin ABD. Using an in vitro competition assay, we could show that β4 can compete out the plectin ABD fragment from its association with F-actin. The ability of β4 to prevent binding of F-actin to plectin explains why F-actin has never been found in association with hemidesmosomes, and provides a molecular mechanism for a switch in plectin localization from actin filaments to basal intermediate filament–anchoring hemidesmosomes when β4 is expressed. Finally, by mapping of the COOH-terminally located binding site for several different intermediate filament proteins on plectin using yeast two-hybrid assays and cell transfection experiments with MD-EBS keratinocytes, we confirm that plectin interacts with different cytoskeletal networks.